Traditional Chinese medicine treatment in a patient with severe COVID-19 - Ming Zhong; Shiqi Sun; Fengjun Zhang; Wei Zhang (Medicine, 2026)
Rationale: Elderly patients with severe COVID-19 frequently develop chronic critical illness marked by prolonged ventilation, multidrug-resistant infections, enteral-nutrition (EN) intolerance, and persistent inflammation–immunosuppression–catabolism syndrome, making liberation from the ventilator and recovery difficult. Integrative Chinese and Western medicine (ICWM) is hypothesized to modulate immunity and the gut–lung axis and to stabilize frail physiology during long ICU courses. Patient concerns: An 87-year-old man with >10-year Parkinson’s disease experienced septic shock, invasive ventilation, and tracheotomy after COVID-19, prompting a request for ICWM. Diagnoses: Severe pneumonia due to COVID-19 (CURB-65 score of 3); multiple organ dysfunction syndrome (respiratory failure, acute renal failure, and acute heart failure); sepsis; malnutrition; Parkinson’s disease; and lower extremity venous thrombosis. The traditional Chinese medicine diagnosis was based on “epidemic disease,” with dampness toxin stagnation in the lung, and spleen and kidney deficiency. Interventions: A multidisciplinary team delivered individualized ICWM aligned with the “Shanghai Expert Consensus” and the traditional Chinese medicine principle of “benefiting qi and strengthening the body.” Prescriptions were dynamically adjusted to syndrome evolution and to gastrointestinal tolerance, successively including Buzhong Yiqi decoction, Shenling Baizhu powder, Weijing decoction, Tounong decoction, and Shengxian decoction; when gastrointestinal absorption was limited or shock was present, intravenous Shenfu injection was added. Standard care comprised culture-guided antimicrobials, bronchoscopy-assisted secretion clearance, invasive ventilatory support, and nutrition therapy with EN. The ICWM plan was titrated specifically to address EN-intolerance diarrhea and to support nutritional rehabilitation. Outcomes: After treatment, intolerance symptoms improved; sputum cultures converted to negative by ICU day 41. The patient weaned from mechanical ventilation and the tracheal tube 10 days later, and remained afebrile without productive cough, enabling discharge to home convalescence. Lessons: This case highlights the need for ICWM in critically ill patients, especially in those with chronic critical illness and persistent inflammation–immunosuppression–catabolism syndrome.